KERNEL NONPARAMETRIC REGRESSION FOR THE MODELIZING OF THE PRODUCTIVITY WETLAND PADDY - Tiani Wahyu Utami; Martyana Prihaswati; Vega Zayu Varima (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2018)
Nonparametric regression can be used when the relationship between the response variable and the predictor variables have an unknown pattern form the regression curve. One of the method that can be used to predictproductivity of the wetland paddy is a nonparametric regression kernel. In kernel regression, there are severaltypes of estimator that can be used to modelling productivity of wetland paddy in Central Java, one of which isNadaraya-Watson estimator. Variables used in the study of the productivity of rice as the response variable,while the predictor variables that harvested area, production and rainfall. Based on estimates indicate that thekernel nonparametric regression optimum bandwidth value 1.2 and GCV = 1.7577. The coefficient ofdetermination (R2) of 94.23% and MSE of 0.8560. Keywords: Kernel Nonparametric Regression, Productivity, Wetland Paddy